Pharmacokinetic Monitoring of Levetiracetam in Portuguese Refractory Epileptic Patients: Effect of Gender, Weight and Concomitant Therapy - Silva, Rui (2020)
Levetiracetam is a second-generation antiepileptic drug, widely used in the treatment of focal and generalized epilepsy due to its pharmacokinetic and safety profiles. Its pharmacokinetic monitoring is ascribed as useful to personalize its dosing regimen. The aim of the present study was to describe, for the first time, the pharmacokinetics of levetiracetam in Portuguese refractory epileptic patients. Therefore, a retrospective study was carried out on 65 Portuguese refractory epileptic patients (pharmacokinetic study: 48; validation study: 17) admitted to the Refractory Epilepsy Centre of the Centro Hospitalar e Universitário de Coimbra, Coimbra, Portugal. The pharmacokinetic parameters of levetiracetam were estimated by applying a one-compartment model with first-order absorption and elimination analysis. Male patients showed higher distribution volume (Vd/F) and oral clearance (CL/F) than female patients (median Vd/F: 52.40 L in males and 38.60 L in females, p = 0.011; median CL/F: 4.71 L/h in males and 3.91 L/h in females, p = 0.028). Higher values of Vd/F (p = 0.026) and CL/F (p = 0.003) were also found in overweight patients relative to normal weight and obese patients. Carbamazepine was the co-administered antiepileptic drug that mostly affected the pharmacokinetics of levetiracetam, increasing both Vd/F (61.30 L with carbamazepine and 39.10 L without carbamazepine, p = 0.007) and CL/F (6.71 L/h with carbamazepine and 3.91 L/h without carbamazepine, p < 0.001). The pharmacokinetics of levetiracetam was affected by gender, body mass index, and co-administration of carbamazepine. This study highlights the impact of several factors on the CL/ and Vd/F of levetiracetam when administered to refractory epileptic patients. The importance of its pharmacokinetic monitoring in clinical pharmacy stands out, thereby enabling the optimization of antiepileptic drug therapy.